High-Pressure Pool-Boiling Heat Transfer Enhancement Mechanism on Sintered-Particle Wick Surface - Dahariya, Smreeti; Patel, Nill; Egbo, Munonyedi K.; Hwang, Gisuk; Betz, Amy Rachel (Frontiers in Mechanical Engineering, 2020)
We experimentally study high-pressure pool-boiling heat transfer enhancement using a copper sintered-particle wick structure in water. The wicks are fabricated using the multi-step sintering process using 200 μm sintered copper powder. Thermophysical properties of water change at elevated pressure, therefore changing the bubble dynamics. For the single-layer wick, Critical Heat Fluxes (CHF) of 179.63, 182.42, and 198.16 W/cm2 are found at 0, 103.4, and 206.8 kPa, respectively. The maximum CHF is found at 206.8 kPa with the wick superheat of 9.9 K. A 110% enhancement is found in the CHF for 206.8 kPa, compared to 0 kPa. We observed a CHF 1.8 times higher compared to the plain surface at 0 kPa. The maximum Heat Transfer Coefficient (HTC) of 252.46 W/cm2 K is found at a heat flux of 100 W/cm2 and a pressure of 206.8 kPa. The high-pressure pool-boiling result for the single-layer wick shows that the heat transfer coefficient is enhanced by 100% compared to 0 kPa. We suggest the reasons for enhancement of the pool-boiling performance is primarily due to high rate of bubble generation, high bubble release frequency, and reduced thermal-hydraulic length modulation, and enhanced thermal conductivity due to the sintered wick layer. Our analysis suggests that the Rayleigh-critical wavelength decreases by 4.67% with varying pressure, which may cause the bubble pinning between the sintered particles and prevents bubble coalescence. Similarly, the role of pressure in enhancing heat transfer compared to the effect of the wicking layer is also analyzed and found that the critical flow length, λu reduces by three times for 200 μm diameter particles. We suggest that the porous wick layer provides a capillary-assist to liquid flow effect, and delays the surface dry out. The pressure and surface modification amplify the boiling heat transfer performance. All these reasons may contribute to the CHF and HTC enhancement in the wicking layer at high-pressure.